Gramsci lettore, interprete e diffusore di Marx - Pietro Maltese (Firenze University Press, 2019)
The aim of this article is to investigate the Gramsci's interpretation of Marx, emphasizing both a series of training initiatives promoted by the Sardinian intellectual in order to spread and popularize his thought. Gramsci identifies some pedagogical consequences of the education principle of the "philosophy of praxis".